Symposium 2: Blended Simulation Based Medical Education: A Durable Network for Learning? - Shahoumian, Armineh; Parchoma, Gale; Hanson, Jacky (Proceedings of the International Conference on Networked Learning, 2014)
Simulation based medical education (SBME) is gradually becoming an inseparable part of medical and Professionals Allied to Medicine (PAM) education. The demand to use this training approach in healthcare is increasing every year to meet the Department of Health’s Standards for Better Health (NESC, 2008). As an alternative training approach SBME provides medical students and practitioners with near real-life opportunities to practice and improve clinical and non-clinical skills and improve health care services as a result. Although SBME is already a very popular training approach, Kneebone (2005) argues it is “often accepted uncritically, with undue emphasis being placed on technological sophistication at the expense of theory-based design” (p.549). SBME is “a complex service intervention” (McGaghie, 2009, p.50), which includes much more than a series of advanced technologies utilised for simulating an event. SBME is actualised by a network of closely knit human, non-human, and “conceptual and symbolic” (Bleakley, 2012, p.464) actors that work in an interrelated manner “as a basis to promoting learning and innovation” (Bleakley, p.464). It is not just the sophistication of the technology that supports learning but the dialogic relation of all the actors involved in creating the opportunities for learning. What is required to develop a ‘healthy’ and ‘growing’ network that promotes learning and innovation (Bleakley, 2012) or hinder effective learning hasn’t widely been investigated. Bleakley argues that actor network theory (ANT) “serves to repair the historical separation of theory and practice” (p. 465). To understand SBME as a complex process involving technology, people, objects, artefacts, actions, and places, ANT may introduce new insight, “an interruption or intervention, a way to sense and draw nearer” (Fenwick & Edwards 2010: ix) to the phenomenon of SBME. This paper expands the understanding of how actors interact with each other within a network and the practices that support/hinder blended learning in the Lancashire Teaching Hospitals NHS Trust (LTHTR) Simulation Centre (SC). Outcomes provide insight into the design of a simulation session, describe the assemblage of a blended learning in SBME (B-SBME) actor network, and illustrate an example of the network effects of mediators’ and intermediaries’ capacities to form alliances between a B-SBME networked assemblage and broader Trust networks.